The Influence of Non Physical Work Environment and Job Satisfaction on Employee Performance PT. Sinar Sosro Palembang - Willy Anggraini (International Journal of Marketing & Human Resource Research, 2022)
This study aims to analyze the effect of non-physical work environment and job satisfaction on the performance of employees of PT. Sinar Sosro Palembang. This study uses primary data and secondary data sources. Respondents in this study were 47 respondents. The analytical method used in this research is multiple linear regression. The results showed that the non-physical work environment had a significant positive effect on the performance of PT. Sinar Sosro Palembang. While job satisfaction has no effect on the performance of employees of PT. Sinar Sosro Palembang. This research is useful for companies to pay more attention to the non-physical work environment so that employee performance can continue to be improved.